Peran pesantren dalam pemberdayaan ekonomi umat di Indonesia - Muhammad Anwar Fathoni; Ade Nur Rohim (Proceeding of Conference on Islamic Management, Accounting, and Economics, 2019)
The development of Islamic boarding schools in Indonesia have experienced rapid growth. Today, boarding schools are not only identical to with religious education institutions, but they are also expected to contribute to the economy of people’s life. The purpose of this study is to analyze the role of Islamic boarding schools in the effort of empowering economy of the people/community. This research is a literature study that uses a qualitative descriptive approach. This study found that Islamic boarding schools have sufficient resources and capital to become the basis of the people's economic empowerment. With these resources and capital, Islamic boarding schools can carry out various activities oriented towards the economic empowerment of the surrounding community.